Secret kingdom / Pixie princess - Banks Rosie 1914-2014; Rosie Banks (London : Orchard Books, 2014)
The fourth brilliant Secret Kingdom bumper special - two magical stories in one! Jasmine, Ellie and Summer are thrilled to be visiting Trixibelle's home for a special pixie celebration! But evil Queen Malice is determined to ruin the fun...and steal the crown of the mysterious Pixie Princess. Can the girls stop the queen's wicked plans and save the pixies' Heart Tree home?
M
710